Isolation and Identification of Escherichia coli O157:H7 Lytic Bacteriophage from Environment Sewage - Tessa Sjahriani; Eddy Bagus Wasito; Wiwiek Tyasningsih (International Journal of Food Science)
Escherichia coli O157:H7 is one of the pathogenic bacteria causing foodborne disease. The use of lytic bacteriophages can be a good solution to overcome the disease. This study is aimed at isolating lytic bacteriophages from environmental sewage with E. coli O157:H7 bacterial cells. The sample used in this study was eight bacteriophages, and the technique used in identifying E. coli O157:H7 carriers of the stx1 and stx2 genes was PCR. The double layer plaque technique was used to classify bacteriophages. Plaque morphology, host specificity, and electron micrograph were used to identify the bacteriophages. The result obtained plaque morphology as a clear zone with the largest diameter size of 3.5 mm. Lytic bacteriophage could infect E. coli O157:H7 at the highest titer of 10×108 PFU/mL. Bacteriophages have been identified as Siphoviridae and Myoviridae. Phage 3, phage 4, and phage 8 could infect Atypical Diarrheagenic E. coli 1 (aDEC1) due to their host specificity. The Friedman statistical tests indicate that lytic bacteriophage can significantly lyse E. coli O157:H7 (p=0.012). The lysis of E. coli O157:H7 by phage 1, phage 2, phage 3, and phage 5 bacteriophages was statistically significant, according to Conover’s posthoc test (p<0.05). The conclusion obtained from this study is that lytic bacteriophages from environmental sewage could lyse E. coli O157:H7. Therefore, it could be an alternative biocontrol agent against E. coli O157:H7 that contaminates food causing foodborne disease.